COOPERATIVE LEARNING VS COLLABORATIVE LEARNING - admin admin; Khoirul Anwar (Universitas Muhammadiyah Gresik, 2013)
We often recognize that good teaching is capable of stimulating individual potency through optimizing the power of group learning. Many education experts also agree that the learning groups are very much beneficial for learners primarily on cognitive and affective development. Two approaches are often raised and many practitioners of education refer to the model of cooperative learning and collaborative learning. This paper further discusses the basic principles and the different uses of the two approaches. The author hopes this paper can provide appropriate information on the use of the two learning approaches.